Implementation of The Independent Curriculum in Class V of SD Alkhairaat 2 Palu - Febriawati, Titin; Herlina, Herlina; Muchdar, Muchdar; Nashrullah, Nashrullah; Nuraini, Nuraini (FKIP - Universitas Riau, 2025)
The objectives of this study are: 1) to find out how to implement the independent curriculum in class V of Sd Alkhairaat 2 Palu, 2) to find out the obstacles faced in implementing the Independent curriculum in class V of Sd Alkhairaat 2 Palu. This study uses qualitative research with a phenomenological approach. The results of this study show that the implementation of the Independent Curriculum in grade V of Sd Alkhairaat 2 Palu has 4 stages, namely the planning stage, the implementation stage, the evaluation stage and the follow-up plan which obtained a fairly good category score with a percentage of 68%. The obstacles obtained in implementing the independent curriculum in grade V of Sd Alkhairaat 2 Palu include the lack of facilities and infrastructure facilities and related to the conditions and support from students. So it can be concluded that there are four stages in implementing the Independent Curriculum in learning, namely the planning stage, the implementation stage, the evaluation/assessment stage and the follow-up plan. These four stages have been carried out quite well in grade V of SD Alkhairaat 2 Palu. However, in the process of implementing the Independent Curriculum, there are several obstacles faced, including: 1) related to facilities and infrastructure, and 2) conditions and support from students.